Featured Cover. Issue 6 (18th May 2022) - Oh, Myeongchan; Lee, Jehyun; Kim, Jin‐Young; Kim, Hyun‐Goo
Abstract : The cover image is based on the Research Article Machine learning‐based statistical downscaling of wind resource maps using multi‐resolution topographical data by Myeongchan Oh et al., https://doi.org/10.1002/we.2718 .